Local Languages and Education Amidst Conflict and Federal Aspirations in Myanmar - Nicolas Salem-Gervais; Amber Spreelung; Hawng Tsai; Pau Sian Lian (Moussons)
Myanmar is a country of complex ethnic and linguistic diversity, whose independence was founded upon federal principles and compromises. Language-in-education policy has remained a contentious issue since, especially under successive military juntas that had systematically restricted the use of ethnic minority languages in formal education. In contrast, the reform period from 2011 to 2021 saw slow but notable progress: by 2020, 64 minority languages had been introduced as subjects in government schools, and collaboration between non-state ‘ethnic education providers’—often affiliated with ‘ethnic armed organisations’—and the Ministry of Education was gradually improving. However, the 2021 military coup disrupted these advancements, upending Myanmar’s political landscape and triggering conflicts across the country. The coup has also intensified calls for a fundamental reconfiguration of Myanmar’s federal system, while leading to considerably increasing enrolments in non-state education programs, including both longstanding and newly established systems linked to specific ethnic identities. Drawing on a literature review, historical analysis, examination of the current situation, and three case-studies, this article critically assesses the changing role of local languages in education in post-coup Myanmar, highlighting both emerging opportunities and persistent challenges.